Learning to Labour: "Native" Orphans in Colonial India, 1840s–1920s. (April 2020) - Soni,
Abstract: To this day, the history of indigenous orphans in colonial India remains surprisingly understudied. Unlike the orphans of Britain or European and Eurasian orphans in the colony, who have been widely documented, Indian orphans are largely absent in the existing historiography. This article argues that a study of "native" orphans in India helps us transcend the binary of state power and poor children that has hitherto structured the limited extant research on child "rescue" in colonial India. The essay further argues that by shifting the gaze away from the state, we can vividly see how non-state actors juxtaposed labour and education. I assert that the deployment of child labour by these actors, in their endeavour to educate and make orphans self-sufficient, did not always follow the profitable trajectory of the state-led formal labour regime (seen in the Indian indenture system or early nineteenth-century prison labour). It was often couched in terms of charity and philanthropy and exhibited a convergence of moral and economic concerns.